Driving multi-electron reactions with photons: dinuclear ruthenium complexes capable of stepwise and concerted multi-electron reduction - Wouters, Kelly L. (2006)
Using biological precedents, it is expected that concerted, multi-electron reduction processes will play a significant role in the development of efficient artificial photosynthetic systems. We have found that the dinuclear ruthenium complexes [(phen)₂Ru(tatpp)Ru(phen)₂⁴⁺ (P) and [(phen)₂Ru(tatpq) Ru(phen)₂]⁴⁺ (Q) undergo photodriven 2- and 4-electron reductions, respectively, in the presence of a sacrificial reductant. Importantly, these processes are completely reversible upon exposure to air, and consequently, these complexes have the potential to be used catalytically in multi-electron transfer reactions. A localized molecular orbital description of the ligands and complexes is used to explain both the function and spectroscopy of these complexes. In both complexes, the reducing equivalents are stored in the π* orbitals of the bridging ligands and depending on the solution pH, various protonation states of the reduced species of P and Q are obtained. Under basic conditions, the photochemical pathway favors sequential single-electron reductions, while neutral or slightly acidic conditions give rise to proton-coupled multi-electron transfer. In fact, at sufficiently acidic pH, only a coupled two-electron, 2-proton process is seen. Few molecular photocatalysts are capable of proton-coupled multi-electron transfer, which is believed to be a fundamental component of light-activated energy storage in nature.